1995
DOI: 10.1002/hep.1840210423
|View full text |Cite
|
Sign up to set email alerts
|

Induction of metallothionein gene expression by epidermal growth factor and its inhibition by transforming growth factor-β and dexamethasone in rat hepatocytes

Abstract: Metallothionein (MT) is a small cysteine-rich protein thought to be mainly involved in metal regulation and detoxification. The implication of MT in cell growth and differentiation has also been suggested. This latter hypothesis was further investigated in adult rat hepatocytes induced to proliferate by epidermal growth factor (EGF). Exposure of hepatocytes to EGF resulted in significant increases (approximately twofold) in MT protein and MT-1 messenger RNA (mRNA) levels, which were maximal after 48 hours. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
(6 reference statements)
1
5
0
Order By: Relevance
“…The HepG2 cells that were used here are adherent cells which were seeded from confluent flasks and are so likely to have been at least partially synchronized in the cell cycle and could so produce a simultaneous rise in the MT just prior to cell division as seen for other cells [26]. MT is an important housekeeping gene and induction of growth in rat hepatocytes has been shown to induce high levels of mRNA which were maximal at 48 h. It was also shown that the effects of growth and metals were additive which would support the observations that we have made here [27].…”
Section: Discussionsupporting
confidence: 84%
“…The HepG2 cells that were used here are adherent cells which were seeded from confluent flasks and are so likely to have been at least partially synchronized in the cell cycle and could so produce a simultaneous rise in the MT just prior to cell division as seen for other cells [26]. MT is an important housekeeping gene and induction of growth in rat hepatocytes has been shown to induce high levels of mRNA which were maximal at 48 h. It was also shown that the effects of growth and metals were additive which would support the observations that we have made here [27].…”
Section: Discussionsupporting
confidence: 84%
“…Members of the MT family were also potently induced by EGF. Whilst induction of MT1 expression by EGF has been shown in rat hepatocytes [41], this is the first report of MT1 (and MT3) induction by EGF in human epithelial cells. Since the altered expression of MT family members has been implicated in neoplasia and drug resistance [42,43], it will be interesting to investigate whether MT expression is linked to deregulated GF signalling in cancer.…”
Section: Discussionmentioning
confidence: 89%
“…The implications are based on research using isolated rat hepatocytes that were induced to proliferate with epidermal growth factor. 27 The proliferative activity in this system was accompanied by appreciable increases in MT-1 mRNA and MT-protein within 48 hours. This was augmented by addition of zinc sulfate.…”
Section: Metallothioneins and Growth Factorsmentioning
confidence: 81%
“…Earlier work suggests that cytokines and growth factors are implicated in the activation of the MT‐gene in wounded tissue. The implications are based on research using isolated rat hepatocytes that were induced to proliferate with epidermal growth factor 27 . The proliferative activity in this system was accompanied by appreciable increases in MT‐1 mRNA and MT‐protein within 48 hours.…”
Section: Metallothioneins and Growth Factorsmentioning
confidence: 99%